IMPROVING PROCEDURE TEXT WRITING ABILITY WITH THE PAIR CHECKS LEARNING MODEL IN CLASS XI CULINARY ART OF VOCATIONAL HIGH SCHOOL WIRA BHAKTI - Mas Kusumaningrat Cokorda Istri; Putu Agus Permanamiarta (Stilistika : Jurnal Pendidikan Bahasa dan Seni, 2023)
This study aims to determine the increase in the ability to write procedural texts using the pair checks learning model in class XI culinary art of Vocational High School Wira Bhakti. The method used in this research is descriptive method. The descriptive method is related to the explanation of social phenomena to the observed subjects. The techniques used in this research are observation, documentation study, and tests. The results of the ability to write procedural texts using the pair check learning model for class class XI culinary art of Vocational High School Wira Bhakti in cycle I was 72.88% and in cycle II the student score was 80.45%. It can be concluded that the application of the pair check learning model is able to improve the ability to write procedural texts in English for class XI culinary art of Vocational High School Wira Bhakti.